2023
DOI: 10.5194/egusphere-2022-1496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproducibility of the Wet Part of the Soil Water Retention Curve: A European Interlaboratory Comparison

Abstract: Abstract. The soil water retention curve (SWRC) is a key soil property required for predicting basic hydrological processes. SWRC is often obtained in laboratory with non-harmonized methods. Moreover, procedures associated to each method are not standardized. This can induce a lack of reproducibility between laboratories using different methods and procedures or using the same methods with different procedures. The goal of this study was to estimate the inter/intralaboratory variability of the measurement of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Furthermore, the temperature and relative humidity in the laboratory impact the measurements by altering the surface tension of the water and the vapor fluxes in the sample during equilibration (Hopmans and Dane, 1986). In a recent study on the reproducibility of the wet part of the soil water retention curve Guillaume et al (2023) conducted an inter-and intra-laboratory method comparison and found that both inter-and intralaboratory variability can be a substantial source of scatter and error in the data, even when methods have been harmonised.…”
Section: Harmonization and Standardization Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the temperature and relative humidity in the laboratory impact the measurements by altering the surface tension of the water and the vapor fluxes in the sample during equilibration (Hopmans and Dane, 1986). In a recent study on the reproducibility of the wet part of the soil water retention curve Guillaume et al (2023) conducted an inter-and intra-laboratory method comparison and found that both inter-and intralaboratory variability can be a substantial source of scatter and error in the data, even when methods have been harmonised.…”
Section: Harmonization and Standardization Of Methodsmentioning
confidence: 99%
“…The effect on PTFs, however, remains largely unknown. While inter-laboratory comparisons exist for textural analysis, the same is very rare for hydro-physical properties such as retention curve or hydraulic conductivity (Guillaume et al, 2023). This type of exercise requires reference samples, which drain over predefined pressure head ranges, sufficiently enough so that inter-and intra-laboratory measurement uncertainty may be disentangled.…”
Section: Harmonization and Standardization Of Methodsmentioning
confidence: 99%
“…In the example of Figure 2, but also in the other examined layers, differences between methods and variability due to replication can be observed. Variability of this order of magnitude may be caused by hysteresis, equipment calibration, or other sources (Gubiani et al, 2013;Guillaume et al, 2023;Schelle et al, 2013). It will determine the standard deviation of fitted parameters and the uncertainty of modeling results.…”
Section: Wet Yearmentioning
confidence: 99%